2009
DOI: 10.1007/s11205-008-9434-1
|View full text |Cite
|
Sign up to set email alerts
|

Relatively Different? How do Gender Differences in Well-Being Depend on Paid and Unpaid Work in Europe?

Abstract: Well-being, Paid working hours, Housework hours, Gender, Gender attitudes, Social comparison, Europe,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 29 publications
0
50
0
1
Order By: Relevance
“…It is likely that a number of other factors will have affected these relationships, including whether the woman’s husband or partner held traditional or egalitarian GRAs (although previous studies, including analyses of the BHPS find moderate correlations between the GRAs of men and their wives or partners [10, 68]), the nature of the woman’s employment (in particular whether full- or part-time) and her other roles. The authors of one paper which found no evidence that lack of fit between attitudes and behaviour impacted on marital dissatisfaction suggested that such inconsistencies may be tolerated as ‘unavoidable consequences of individual circumstances’ (p. 183) [33], while those of the two other analyses with similar findings provide no explanations [5, 25]. What is interesting, is that it was the youngest age-group of women who showed most evidence of greater distress when GRAs and actual roles conflicted.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that a number of other factors will have affected these relationships, including whether the woman’s husband or partner held traditional or egalitarian GRAs (although previous studies, including analyses of the BHPS find moderate correlations between the GRAs of men and their wives or partners [10, 68]), the nature of the woman’s employment (in particular whether full- or part-time) and her other roles. The authors of one paper which found no evidence that lack of fit between attitudes and behaviour impacted on marital dissatisfaction suggested that such inconsistencies may be tolerated as ‘unavoidable consequences of individual circumstances’ (p. 183) [33], while those of the two other analyses with similar findings provide no explanations [5, 25]. What is interesting, is that it was the youngest age-group of women who showed most evidence of greater distress when GRAs and actual roles conflicted.…”
Section: Discussionmentioning
confidence: 99%
“…Most research fi nds that women's wellbeing decreases with increasing hours of housework and increases with longer hours in paid employment (Boye 2009 ;Mencarini and Siron 2012 ). The same is not the case for men.…”
Section: Unpaid Work and Wellbeingmentioning
confidence: 99%
“…The same is not the case for men. Many studies fi nd no association between housework and men's wellbeing and only limited evidence of links between employment hours and men's wellbeing (Boye 2009 ), possibly because of minimal variation in paid and unpaid work hours for men. As Boye ( 2009 ) points out, this may vary with gender attitudes or preferences around working time.…”
Section: Unpaid Work and Wellbeingmentioning
confidence: 99%
“…Findings from the European Social Survey (ESS), which includes Austria, Belgium, the Czech Republic, Denmark, Estonia, Finland, France, Germany, Greece, Hungary, Iceland, Luxembourg, the Netherlands, Norway, Poland, Portugal, Slovakia, Slovenia, Spain, Sweden, Switzerland, Turkey, Ukrain, and the United Kingdom, suggests that these additional demands on women may affect their psychological well‐being. Although men's well‐being was not related to the number of hours they spent engaged in paid work or housework, women's well‐being was positively related to hours engaged in paid work and was negatively related to hours engaged in housework (Boye, 2009). Unfortunately, this extra burden faced by many employed women (but fewer employed men) is rarely realized or acknowledged by others.…”
Section: Policy Implicationsmentioning
confidence: 99%